Paige Nicholas: capstone - Nicholas, Paige, artist (Colorado State University. Libraries, 2025)
The artist's statement: Art has always been a way for me to express thoughts and feelings that can be hard to put into words. It's a personal and creative outlet where I can explore different ideas, stories, and emotions. Every piece made holds meaning for me, whether it's connected to a memory, a moment of inspiration, or something I'm still trying to understand. I work with a variety of materials, depending on what I'm creating. Sometimes I paint, ink, watercolor, or charcoal, and other times I enjoy digital tools or mixed media. I experiment and see how different textures, colors, and techniques come together. The process often starts with sketches or quick notes, and then I build on those ideas until the final piece feels right. Much of my inspiration comes from everyday life— people, nature, music, dreams, and even small quiet moments. I'm also drawn to themes like identity, emotion, and storytelling. I want my art to connect with others, to spark curiosity or offer a sense of understanding. Overall, my work represents a journey—of exploring who I am and how I see the world. Thank you for taking the time to view it. I hope you find something in it that speaks to you.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design